Interactive Teaching Module Design Based on Structural Linguistics: For Language Education Students - Pande Gede Brahmandika; Ida Bagus Putrayasa; I Nengah Suandi (Journal of Practice Learning and Educational Development, 2025)
This study aims to design an interactive teaching module based on structural linguistics intended for students of the Language Education study program. The background of this study is based on the need for learning media that is able to integrate structural linguistics theory contextually and applicatively in the language learning process. The method used in this study is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The developed module contains phonology, morphology, syntax, and semantics materials that are systematically arranged with a structural approach, and are equipped with interactive features such as practice questions, learning videos, and language structure analysis simulations. The trial results show that this module is considered effective in improving students' understanding of the basic concepts of structural linguistics and is able to encourage independent learning. Thus, this teaching module can be an innovative alternative in supporting the mastery of structural linguistics theory and practice for prospective language educators.